Communication between host organism and cancer cells is transduced by systemic sphingosine kinase 1/sphingosine 1‐phosphate signalling to regulate tumour metastasis - Suriyan Ponnusamy; Shanmugam Panneer Selvam; Shikhar Mehrotra; Toshihiko Kawamori; Ashley J. Snider; Lina M. Obeid; Yuan Shao; Roger Sabbadini; Besim Ogretmen (EMBO Molecular Medicine)
Abstract Mechanisms by which cancer cells communicate with the host organism to regulate lung colonization/metastasis are unclear. We show that this communication occurs via sphingosine 1‐phosphate (S1P) generated systemically by sphingosine kinase 1 (SK1), rather than via tumour‐derived S1P. Modulation of systemic, but not tumour SK1, prevented S1P elevation, and inhibited TRAMP‐induced prostate cancer growth in TRAMP+/+SK1−/− mice, or lung metastasis of multiple cancer cells in SK1−/− animals. Genetic loss of SK1 activated a master metastasis suppressor, Brms1 (breast carcinoma metastasis suppressor 1), via modulation of S1P receptor 2 (S1PR2) in cancer cells. Alterations of S1PR2 using pharmacologic and genetic tools enhanced Brms1. Moreover, Brms1 in S1PR2−/− MEFs was modulated by serum S1P alterations. Accordingly, ectopic Brms1 in MB49 bladder cancer cells suppressed lung metastasis, and stable knockdown of Brms1 prevented this process. Importantly, inhibition of systemic S1P signalling using a novel anti‐S1P monoclonal antibody (mAb), Sphingomab, attenuated lung metastasis, which was prevented by Brms1 knockdown in MB49 cells. Thus, these data suggest that systemic SK1/S1P regulates metastatic potential via regulation of tumour S1PR2/Brms1 axis.